2019
DOI: 10.7759/cureus.5166
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Association of Elevated Liver Transaminases in Type 2 Diabetes Mellitus Patients in Jeddah, Saudi Arabia

Abstract: BackgroundThis study investigated the prevalence and association of liver transaminases in type 2 diabetes mellitus (T2DM) patients at King Abdulaziz University Hospital (KAUH), Jeddah, Saudi Arabia.MethodsThis retrospective, cross-sectional study was carried out on 211 T2DM patients at KAUH in 2017, and the Research Ethics Committee of KAUH approved this study. The data were analyzed on SPSS 21 (IBM Corp., Armonk, NY, US). The association of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
2
9
1
2
Order By: Relevance
“…This is partly in agreement with the findings of (28) which reported significantly higher mean age in diabetic males than in female; significantly higher BMI in females than in male diabetic participants (28). They further recorded significantly higher mean fasting blood glucose level in female diabetic participants than in their male counterpart; a report which is in contrast to the finding in this study (28). There were stronger positive correlation between Weight Vs BMI (r=0.834; p=0.000), followed by Lipase Vs Amylase (r=0.767; p=0.000), least between Age Vs BMI (r=0.353; p=0.022) but weaker negative associations exist between Height Vs BMI (r=-0.490; p=0.001) and Weight Vs FBS (r=-0.325; p=0.036) in the diabetic subjects.…”
Section: Discussioncontrasting
confidence: 99%
“…This is partly in agreement with the findings of (28) which reported significantly higher mean age in diabetic males than in female; significantly higher BMI in females than in male diabetic participants (28). They further recorded significantly higher mean fasting blood glucose level in female diabetic participants than in their male counterpart; a report which is in contrast to the finding in this study (28). There were stronger positive correlation between Weight Vs BMI (r=0.834; p=0.000), followed by Lipase Vs Amylase (r=0.767; p=0.000), least between Age Vs BMI (r=0.353; p=0.022) but weaker negative associations exist between Height Vs BMI (r=-0.490; p=0.001) and Weight Vs FBS (r=-0.325; p=0.036) in the diabetic subjects.…”
Section: Discussioncontrasting
confidence: 99%
“…The pathophysiological mechanism responsible for these elevations in transaminases activities may indicate inflammation status that systemically impairs insulin signaling in the liver. It was reported that insulin resistance is caused by ALT regardless of age, body mass index, or gender [14]. A direct linkage was reported between transaminase enzymes elevation and hepatocyte injury.…”
Section: Serum Levels Of Liver Function Markersmentioning
confidence: 98%
“…Hasil analisis hubungan yang dilakukan antara kadar ALT dengan kadar kolesterol total, kadar kolesterol HDL, kadar kolesterol LDL, dan kadar trigliserida menggunakan uji korelasi Spearman rank, menunjukkan bahwa tidak terdapat hubungan bermakna dan nilai korelasi yang menunjukkan hubungan yang negatif. Hasil penelitian ini sejalan dengan penelitian yang dilakukan di Arab Saudi oleh Alzahrani et al 12 yang menyatakan bahwa tidak terdapat hubungan bermakna antara peningkatan kadar ALT dengan kadar kolesterol total, HDL, LDL, dan trigliserida. Berbeda halnya dengan penelitian yang dilakukan oleh Al-Jameil et al 13 yang menunjukkan adanya hubungan positif yang bermakna antara peningkatan kadar ALT dengan kadar kolesterol total, LDL, dan trigliserida.…”
Section: Bahasanunclassified
“…Hal ini sejalan dengan penelitian Saligram et al 15 terhadap pasien DM tipe 2 yang baru terdiagnosis yang menunjukkan bahwa tidak terdapat hubungan bermakna antara kadar ALT dengan kadar HbA1C. Hasil penelitian ini juga sejalan dengan penelitian oleh Alzahrani et al 12 yang menyatakan bahwa tidak terdapat hubungan antara peningkatan kadar ALT dengan kadar HbA1c, namun hasil penelitian ini bertolak belakang dengan penelitian yang dilakukan oleh Shahwan et al 14 yang menyimpulkan adanya hubungan antara peningkatan kadar ALT pada pasien dengan kadar HbA1c ≥7%.…”
Section: Bahasanunclassified